The association of host and vector characteristics with Ctenocephalides felis pathogen and endosymbiont infection - Moore, Charlotte; Breitschwerdt, Edward B.; Kim, Lisa; Li, Yiyao; Ferris, Kelli; Maggi, Ricardo; Lashnits, Erin (Frontiers in Microbiology, 2023)
Surveillance of the fleas and flea-borne pathogens infecting cats is important for both human and animal health. Multiple zoonotic Bartonella and Rickettsia species are known to infect the most common flea infesting cats and dogs worldwide: Ctenocephalides felis, the cat flea. The ability of other flea species to transmit pathogens is relatively unexplored. We aimed to determine cat host and flea factors independently associated with flea Bartonella and Rickettsia infection. We also assessed flea and cat infection by flea-host pair and location. To accomplish these aims, we performed qPCR for the detection of Bartonella, hemotropic Mycoplasma, Rickettsia, and Wolbachia DNA using paired cat and flea samples obtained from free-roaming cats presenting for spay or neuter across four locations in the United States. A logistic regression model was employed to identify the effect of cat (sex, body weight, geographic location, and Bartonella, hemotropic Mycoplasma, and Rickettsia spp. infection) and flea (clade and Rickettsia and Wolbachia infection) factors on C. felis Bartonella clarridgeiae infection. From 189 free roaming cats, we collected 84 fleas: Ctenocephalides felis (78/84), Cediopsylla simplex (4/84), Orchopeas howardi (1/84), and Nosopsyllus fasciatus (1/84). Ctenocephalides felis were phylogenetically assigned to Clades 1, 4, and 6 by cox1 gene amplification. Rickettsia asembonensis (52/84) and B. clarridgeiae (16/84) were the most common pathogenic bacteria detected in fleas. Our model identified host cat sex and weight as independently associated with B. clarridgeiae infection in fleas. Rickettsia asembonensis (52/84), Rickettsia felis (7/84) and Bartonella henselae (7/84) were detected in specific clades: R. felis was detected only in Clades 1 and 6 while B. henselae and R. asembonensis were detected only in Clade 4. Wolbachia spp. also displayed clade specificity with strains other than Wolbachia wCfeT only infecting fleas from Clade 6. There was poor flea and host agreement for Bartonella spp. infection; however, there was agreement in the Bartonella species detected in cats and fleas by geographic location. These findings reinforce the importance of considering reservoir host attributes and vector phylogenetic diversity in epidemiological studies of flea-borne pathogens. Widespread sampling is necessary to identify the factors driving flea-borne pathogen presence and transmission.